Mutational analysis of human papillomavirus type 16 E6 demonstrates that p53 degradation is necessary for immortalization of mammary epithelial cells. - Dalal, S (1996)
We have previously demonstrated that normal human mammary epithelial cells (MECs) are efficiently immortalized by human papillomavirus type 16 (HPV16) E6. HPV16 E6 binds to and induces p53 degradation in vitro and induces a marked reduction of p53 protein in MECs. Low-risk HPV6 E6 is defective for p53 binding and degradation in vitro but immortalized MECs at low efficiency. The HPV6 E6-immortalized MECs had markedly reduced levels of p53. To directly investigate whether the ability of HPV16 E6 to stimulate p53 degradation is required for E6-induced immortalization, a series of HPV16 E6 mutants were analyzed for the ability to bind and degrade p53 in vitro, induce a reduction in p53 levels in vivo, and immortalize MECs. We observed that one set of mutants efficiently immortalized MECs, caused a reduction in p53 levels in vivo, and degraded p53 in vitro. Other mutants immortalized MECs with low efficiency and either induced p53 degradation at low levels or were unable to induce p53 degradation in vitro; however, all of the immortal clones displayed low levels of p53. A third class of mutants did not immortalize MECs and failed to induce a reduction in p53 levels in vivo or degrade p53 in vitro. These results demonstrate that a reduction in p53 protein levels due to enhanced degradation is essential for MEC immortalization by HPV16 E6.